Improving The Performance Of Tcp Flows In Wireless Networks By Using Tcp Aware Backpressure And Aodv Algorithms - et. al., Rajan S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensor networks (WSN’s) are a wireless network consisting of spatially spare out. The wireless sensor network is being deployed in many real-time applications such as environmental monitoring, security, surveillance, industrial automation and control. There are many challenges available in the wireless sensor network. They are Quality of Service (QoS), fault tolerance, scalability and maintainability. Here, choose the Quality of Service to measure the performance of Transmission Control Protocol (TCP) flows. Throughput and fairness are present in the parameter Quality of Service. There are two algorithms are used to measure the throughput and fairness. The first algorithm is TCP aware Backpressure and another one is Ad-hoc On Demand Distance Vector (AODV). Contrast these two algorithms which one is giving a better performance of TCP flows.